Bacterial meningitis presenting with a normal cerebrospinal fluid leukocyte count. Issue 5 (May 2022) - van Soest, Thijs M.; Chekrouni, Nora; van Sorge, Nina M.; Brouwer, Matthijs C.; van de Beek, Diederik
Highlights: Patients with bacterial meningitis may present with normal CSF leukocyte counts. In these patients, the CSF protein and Gram stain are important diagnostic tests. Severe pneumococcal meningitis with a fulminant disease course was common (51%). Outcome is often unfavorable (59%) and the mortality rate is high (30%). Abstract: Objectives: We describe clinical characteristics and outcome of adults with bacterial meningitis presenting with a normal CSF leukocyte count. Methods: We studied community-acquired bacterial meningitis with a normal CSF leukocyte count (≤ 5 per mm 3 ) in adults from a prospective nationwide cohort study. Results: From 2006 through 2020, 39 of 2, 357 (2%) episodes presented with a normal CSF leukocyte count. Immunocompromising conditions were present in 19 of 39 patients (49%), compared to 690 of 2303 (30%) in patients with elevated leukocytes ( P = 0.02). The triad of fever, neck stiffness, and altered consciousness was present in 6 of 34 patients (18%). CSF protein was abnormal in 25 of 37 patients (68%). We identified 3 clinical subgroups: those with severe pneumococcal meningitis (20 patients [51%]), with mainly sepsis (8 [21%]), and a miscellaneous group (11 [28%]). All patients with severe pneumococcal meningitis presented with high CSF protein levels and 18 of 19 (95%) had bacteria in the CSF Gram stain. Outcome was unfavorable in 23 of 39 (59%) patients and 12 (31%) died. Conclusion: Patients with bacterial meningitis may present with normal CSF leukocyte counts. In these patients, CSF protein levels and Gram staining are important diagnostic parameters.